Bringing ChatGPT into Arabic Language Learning - Yusuf, Kamal (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
Artificial intelligence (AI) has changed the landscape of education and teaching, and one of the latest innovations that has shocked the world of education is the emergence of ChatGPT. This interactive application allows humans to communicate with computer machines for various purposes, including learning foreign languages. One of the languages that has traditionally been considered difficult to learn is Arabic, but with ChatGPT, learning Arabic has become easier and more affordable. This article aims to describe the various ways in which ChatGPT can be explored in learning Arabic.